2014
DOI: 10.1371/journal.pone.0097902
|View full text |Cite
|
Sign up to set email alerts
|

On the Crucial Cerebellar Wound Healing-Related Pathways and Their Cross-Talks after Traumatic Brain Injury in Danio rerio

Abstract: Upon injury, the direct damage and the subsequent secondary injury in the brain often result in chronic neurological disorders. Due to multifactorial nature of secondary injury and subsequent complex cellular responses, much of the underlying mechanisms are unclear. This study used an adult zebrafish cerebellum injury model to investigate the phenotypes and the secondary injury responses for recovery mechanisms of injured brain. Using the time course microarray analysis, a candidate protein-protein interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…We compared the results with our previous study, "On the Crucial Cerebellar Wound Healing-Related Pathways and Their Cross-Talks after Traumatic Brain Injury in Danio rerio [ 35 ]". We found that there were no intersections between these 2 results.…”
Section: Resultsmentioning
confidence: 99%
“…We compared the results with our previous study, "On the Crucial Cerebellar Wound Healing-Related Pathways and Their Cross-Talks after Traumatic Brain Injury in Danio rerio [ 35 ]". We found that there were no intersections between these 2 results.…”
Section: Resultsmentioning
confidence: 99%
“…The first group was adult zebrafish without lesion as a blank control. The other groups were injured by syringe (27G; Thermo Scientific, USA) to cause lesion in cerebellum [28]. The treatments on adult zebrafish were transplanted with FOXD3-transfected cells or nontransfected cells encapsulated in the chitosan-based self-healing hydrogel.…”
Section: Nerve Functional Rescue In Vivomentioning
confidence: 99%
“…Specifically, dynamic host–pathogen protein–protein interaction networks (HP-PPINs) can be used to bridge the gap between infection-activated molecular mechanisms and physiological phenomena. Moreover, dynamic PPINs quantitatively delineate the effects of current protein levels on the expression of other proteins [ 7 ] and can, therefore, be used to characterize the molecular mechanisms behind the interactions of host and pathogen proteins during the infection process. Hence, relating the infection-activated molecular mechanisms to physiological phenomena using dynamic HP-PPINs may inform biomedical applications from the investigations of HPIs.…”
Section: Introductionmentioning
confidence: 99%